Amphiphilic anthanthrene trimers that exfoliate graphite and individualize single wall carbon nanotubes - Münich, Peter Wilhelm; Pfäffli, Matthias; Volland, Michel; Liu, Shi-Xia; Haener, Robert; Guldi, Dirk Michael (Nanoscale, 2020)
A phosphodiester-linked dialkynyl substituted anthanthrene trimer (1) has been designed and synthesized. Its graphene ribbon like structure is expected to facilitate interactions with nanographene (NG) and single wall carbon nanotubes (SWCNT) to yield novel and stable carbon-based nanomaterials. Interactions with trimer 1 lead to exfoliation of NG and to the individualization of SWCNTs. Phosphate groups, in general, and their negative charges, in particular, render the resulting nanomaterials soluble in ethanol, which is ecologically favourable over DMF required for the processing of pristine NG or SWCNTs. The newly formed nanomaterials were probed by complementary spectroscopic and microscopic techniques. Of particular importance were transient absorption and fluorescence excitation measurements, which revealed an efficient energy transfer within the carbon-based nanomaterials.
CRIS-Team Scopus Importer:2020-01-14

Amphiphilic Zinc Porphyrin Single-Walled Carbon Nanotube Hybrids: Efficient Formation and Excited State Charge Transfer Studies - Menon, Arjun; Münich, Peter Wilhelm; Wagner, Pawel; Officer, David L.; Guldi, Dirk Michael (Small, 2021)
Herein, the microscopic and spectroscopic characterization of a novel non-covalent electron donor−acceptor system, in which three different metalloporphyrins (1, 2, and 3) play the dual role of light harvester and electron donor with SWCNTs as electron acceptor, is described. To this end, microscopy, that is, atomic force microscopy (AFM) and transmission electron microscopy (TEM) corroborate the formation of 1-SWCNT, 2-SWCNT, and 3-SWCNT. Spectroscopy by means of Raman, fluorescence, and transient absorption spectroscopy confirmed efficient charge-transfer interaction from photoexcited metalloporphyrins to SWCNTs in the ground and excited state of 1-SWCNT, 2-SWCNT, and 3-SWCNT. The complementary use of spectroelectrochemical and transient absorption measurements substantiates the formation of one-electron oxidized metalloporphyrins after photoexcitation. Multiwavelength global analysis provides insights into the charge-separation and recombination processes in 1-SWCNT, 2-SWCNT, and 3-SWCNT upon photoexcitation. Notably, both the charge-separation and recombination dynamics are fastest in 2-SWCNT. Importantly, the strongest interactions in the steady-state experiments are associated with the fastest excited state decay in the time-resolved measurements.
CRIS-Team Scopus Importer:2021-01-22
Keywords: carbon nanotubes; charge-transfer interactions; doping; non-covalent functionalization; porphyrins

Interfacing porphyrins and carbon nanotubes through mechanical links - De Juan-Fernandez, Leire; Münich, Peter Wilhelm; Puthiyedath, Arjun; Nieto-Ortega, Belen; Casado, Santiago; Ruiz-Gonzalez, Luisa; Perez, Emilio M.; Guldi, Dirk Michael (Chemical Science, 2018)
We describe the synthesis of rotaxane-type species composed of macrocyclic porphyrin rings mechanically interlocked with SWCNT threads. The formation of mechanically interlocked SWCNTs (MINTs) proceeds with chiral selectivity, and was confirmed by spectroscopic and analytical techniques and adequate control experiments, and corroborated by high-resolution electron microscopy. From a thorough characterization of the MINTs through UV-vis-NIR absorption, fluorescence, Raman, and transient absorption spectroscopy we analyse in detail the electronic interactions of the porphyrins and the SWCNTs in the ground and excited states.
CRIS-Team Scopus Importer:2022-04-14

Mono- And Tripodal Porphyrins: Investigation on the Influence of the Number of Pyrene Anchors in Carbon Nanotube and Graphene Hybrids - Garrido, Marina; Volland, Michel; Münich, Peter Wilhelm; Rodríguez-Pérez, Laura; Calbo, Joaquín; Ortí, Enrique; Herranz, M. ángeles; Martín, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
A series of molecular precursors, containing one (1 and 3) or three (2 and 4) pyrene anchors, covalently linked to porphyrins (free base or Zn), were prepared and characterized. All of them enable their π-πstacking onto low-dimensional nanocarbons including single-walled carbon nanotubes (SWCNTs) and nanographene (NG), their individualization, and their characterization. Microscopic (TEM, AFM) and spectroscopic (steady-state UV-vis and fluorescence, spectroelectrochemistry, and transient absorption measurements) techniques were at the forefront of the characterizations and were complemented by Raman spectroscopy and theoretical calculations. Of great importance is the Raman analysis, which corroborated n-doping of the nanocarbons due to the interactions with 1-4 when probed in the solid state. In solution, the situation is, however, quite different. Efficient charge separation was only observed for the graphene-based system NG/3.
CRIS-Team Scopus Importer:2020-02-04

Photon- and Charge-Management in Advanced Energy Materials: Combining 0D, 1D, and 2D Nanocarbons as well as Bulk Semiconductors with Organic Chromophores - Cadranel, Alejandro; Haines, Philipp; Kaur, Ramandeep; Menon, Arjun; Münich, Peter Wilhelm; Schol, Peter; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
In this contribution, seminal works in the area of photon- and charge-management are highlighted with focus on covalent electron donor-acceptor conjugates built around porphyrins (Ps), on one hand, and 0D, 1D, and 2D nanocarbons, on the other hand. Photons in these conjugates are managed by Ps, while 0D, 1D, and 2D nanocarbons serve as the active component, which enable managing charges. With a few leading examples, it can be explored much beyond the simple photon- and charge-management characterization and emphasize photovoltaics and photocatalysis to convert and store energy. This contribution concludes by highlighting recent progress in mixing and matching the unique charge-management features of nanocarbons in the design of multidimensional nanocarbons.
CRIS-Team Scopus Importer:2020-12-11
Keywords: charge management; nanocarbons; photon management; solar-energy conversion

The Impact of Aggregation on the Photophysics of Spiro-Bridged Heterotriangulenes - Krug, Marcel; Wagner, Maximilian; Schaub, Tobias A.; Zhang, Wen-Shan; Schüßlbauer, Christoph; Ascherl, Johannes D. R.; Münich, Peter Wilhelm; Schroeder, Rasmus R.; Gröhn, Franziska; Dral, Pavlo O.; Barbatti, Mario; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2020)
We report on the impact of the central heteroatom on structural, electronic, and spectroscopic properties of a series of spirofluorene-bridged heterotriangulenes and provide a detailed study on their aggregates. The in-depth analysis of their molecular structure by NMR spectroscopy and X-ray crystallography was further complemented by density functional theory calculations. With the aid of extensive photophysical analysis the complex fluorescence spectra were deconvoluted showing contributions from the peripheral fluorenes and the heteroaromatic cores. Beyond the molecular scale, we examined the aggregation behavior of these heterotriangulenes in THF/H2O mixtures and analyzed the aggregates by static and dynamic light scattering. The excited-state interactions within the aggregates were found to be similar to those found in the solid state. A plethora of morphologies and superstructures were observed by scanning electron microscopy of drop-casted dispersions.
CRIS-Team WoS Importer:2020-07-24

Tuning the Carbon Nanotube Selectivity: Optimizing Reduction Potentials and Distortion Angles in Perylenediimides - Münich, Peter Wilhelm; Schierl, Christoph; Dirian, Konstantin; Volland, Michel; Bauroth, Stefan; Wibmer, Leonie; Syrgiannis, Zois; Clark, Timothy; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
Different water-soluble perylenediimides (PDIs) have been used to individualize and stabilize single-walled carbon nanotubes (SWCNTs) in aqueous media. A key feature of the PDIs is that they can be substituted at the bay positions via the addition of two and/or four bromines. This enables control over structural and electronic PDI characteristics, which prompted us to conduct comparative assays with focus on SWCNTs' chirality and charge transfer. Electrochemical, microscopic, and spectroscopic experiments were used to investigate the SWCNT chiral selectivity of PDIs, on the one hand, and charge-transfer reactions between SWCNTs and PDIs, on the other hand.

Use of alkylated, amphiphilic zinc porphyrins to disperse individualized SWCNTs - Münich, Peter Wilhelm; Wagner, Pawel; Officer, David L.; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2018)
A series of zinc porphyrins, namely ZnPa and ZnPb, which exist predominantly as aggregates, are utilized in a top-down preparation of individualized and stabilized single wall carbon nanotubes (SWCNTs). Sizable interactions in the ground state of the corresponding SWCNT/ZnPa and SWCNT/ZnPb electron donor-acceptor systems lead to charge transfer in the excited state. The product includes the simultaneous reduction of the electron-accepting SWCNTs and the oxidation of the electron-donating ZnPa and ZnPb.
CRIS-Team Scopus Importer:2022-04-14
Keywords: porphyrin; single wall carbon nanotube; spectroscopy